Independence of The Constitutional Court In Judicial Review Related To Constitutional Court Laws - Bambang Sutejo; Shaliha Az-Zahra (IHSA Institute, 2022)
The independence of the Constitutional Court is a guarantee for the rule of law and justice. The principle which states that judges may not examine cases involving themselves (nemo judex idoneus in propria causa) is one way to protect the dignity of the Constitutional Court. However, this is contrary to the authority of the Constitutional Court which has been confirmed by Article 24C of the 1945 Constitution of the Republic of Indonesia, one of which gives the authority to review the Constitution. The problem is also increasing with the absence of external supervision of constitutional judges which has been in effect after the Constitutional Court's Decision No. 1-2/PUUXII/2014, the date of the review of the Constitutional Court Law to date. This research is a normative/doctrinal legal research, which shows that the authority of the Constitutional Court to review the laws governing the Constitutional Court as a constitutional mandate.